Influence of preharvest factors in melon (Cucumis melo L.) production and fruit quality. - Méndez Soto, Carlos Humberto 1961- ([editor no identificado], 1996)
Tesis (Master of Science)--The Pennsylvania State University. College of Agricultural Sciences, 1996.